Downstream passage of radiotagged Atlantic salmon (Salmo salar) smolts at the Holyoke Project, Holyoke, Massacusetts, 1995 - Northeast Utilities Service Company (ScholarWorks@UMass Amherst, 1996)
Downstream fish passage facilities at the Holyoke Project were modified to enhance the passage of Atlantic salmon (Salmo salar) smolts. A pier extension was installed adjacent to the Holyoke Dam bascule gate, the opening of an experimental weir inserted in the bascule gate was moved closer to the Hadley Falls Station intakes, and above-water lighting was added. An intake rack overlay was in place at both Hadley Falls Station units during the first half of this evaluation; the Unit 2 overlay was removed during the second half. Radiotagged, hatchery-reared Atlantic salmon smolts were released upstream of the Project and downstream passage routes were monitored. All releases were conducted after flashboards had been installed on the crest of the dam, closing that passage route. Overall, 63% of the radiotagged smolts that approached Hadley Falls Station passed over the bascule gate weir and 37% passed through the turbines. These results were comparable to results obtained in a 1992 evaluation, when a floating guide wall was present upstream of the intakes. Two-thirds of the radiotagged smolts that passed through the turbines at Hadley Falls Station did so through Unit 1. Removal of the Unit 2 intake rack overlay did not affect the proportion of radiotagged smolts passing through the turbines. Combining data from 1992 and 1995, a statistically significant but weak negative relationship between flow through the station and the proportion of radiotagged smolts passing over the bascule gate/weir was found. The louver/bypass system in the Holyoky Canal passed 91% of the radiotagged smolts entering the canal back to the Hadley Falls Station tailrace. Above-water lighting installed upstream of the canal gatehouse appeared to have raised the proportion of radiotagged smolts entering the canal. When the results of passage through the bascule gate weir and the louver/bypass system were combined, 74% of the radiotagged smolts passed through downstream passage facilities. Smolts passing through the louver/bypass system or through the turbines arrived at a location downstream of the dam more quickly than smolts that had passed through the bascule gate weir.